Evaluation Index System of Enterprise Digital Transformation Based on Balanced Scorecard - Xiaobo Fang, Fangxin Zhang, Minoo Ghoreishi (Forest Chemicals Review)
In order to overcome the shortcomings of only relying on financial indicators to measure the performance of digital transformation of enterprises, this study is based on the Balanced Scorecard, according to the digitization of financial management, customer service digitization, internal process digitization, learning and growth digitization, determine the operational definition and framework of the digital transformation balanced scorecard, an evaluation index system is designed. Through literature review, this study sorts out the relevant theories of enterprise digital transformation and the balanced scorecard, uses the expert fuzzy Delphi method to discuss the performance evaluation indicators of digital transformation, and revises it through the fuzzy Delphi method. A digital transformation performance evaluation index system with 14 indicators, and this evaluation index system is verified through case studies. In the digital transformation evaluation index system, the customer service digital aspect is a relatively important dimension; the investment strategy is a relatively important indicator in the financial digital transformation dimension; customer satisfaction is a relatively important indicator in the customer service digital dimension; The digital full-time department is a relatively important indicator in the digital dimension of internal processes; there is no particularly prominent indicator in the digital learning and growth dimension. In terms of digital transformation, companies should focus on digitizing customer service, focus on information and data related to investment strategies, and pay more attention to improving customer service quality. The problems arise in digital transformation, and then avoid the occurrence of events that lead to ineffective digital transformation. This article expands the research on the Balanced Scorecard. Previous studies have examined the impact of the Balanced Scorecard on managers’ judgment and decision-making performance. Based on case evidence, this paper examines the application of the Balanced Scorecard at different levels within a diversified enterprise. This enriches the researchers’ understanding of the applicability of the Balanced Scorecard.